Análise do desenvolvimento de crianças de um a três anos de idade contaminadas por chumbo. - Almeida, Sandra Helena de (2005)
Lead intoxication can damage children development. There are few researches about the effects of lead intoxication on the overall development of young children. The individuals sampled in this study can be considered as double-risk children, since, besides their poor conditions, they are exposed to environmental pollution. Based on that, the present work aimed: a) to analyze the overall development from 1 to 3 yearsold children exposed to lead, with more than ten microgram per deciliter (µg/dl) of blood lead, and in children free from intoxication (0µg/dl of blood lead) and b) to compare the children development and environmental learning conditions between the Group of lead-intoxicated children and the Group of children without contamination. Forty children from 1 to 3 years-old were used in this study, divided into both groups. The Group 1 was composed by 20 children contaminated by lead, and the Group 2 comprised 20 children free from intoxication. The parents or responsible people answered an Initial Interview Report in order to get familiar sociodemographic information and data about children development. The Portage Operational Inventory POI (Williams & Aiello, 2001) and HOME questionnaire (Bradley & Cadwell, 1984) were adopted to verify the overall children development and their environmental and supporting conditions. To assure parental information about the same issues, a protocol of Backing Interview was performed at the end of analyses. POI observations were carried out in a Childhood Center and at children s houses, whereas the HOME inventory was applied to the parents in their houses, exclusively. The data from the first goal of this research demonstrated developmental differences between children from Group 1 and Group 2, based on POI measures. Individuals from both groups presented cognitive and language deficiencies. Nevertheless, according to statistical tests, these differences would be restricted to the areas: Socialization (p<0,05), besides strong statistical tendencies showing that children from Group 2 presented the expected development for their age related to Cognition (p<0,1) and Language (p<0,1) when compared to children from the Group 1, while children from the Group 1 obtained a better performance related to Self Caring (p<0,05) than children from the Group2. Comparing the child development according to environmental quality, we observed that, based on Total Score, Learning Material and HOME variety, both groups were equally deficient. Differences in environmental quality were found in the following sub-scales: Acceptance (p<0,05), where the children from Group 1 presented the highest scores, and Being Responsive (p<0,1) when children from the Group 2 presented a tendency for better punctuation values. There was a significant association (p<0,05) indicating that the low environmental quality, measured by Total Score from HOME inventory, could have influenced the observed deficient children development in both Groups, with regards to Language, Cognition and Overall Development, as measured by POI. Finally, despite of the presented differences, it is not possible to state that lead, solely, caused the deficiency in the development of contaminated children. Indeed, lead intoxication represents a compound that, associated to other risk factors such as poverty and low environmental quality, can maximize the damages over expected child development in each age class. It is necessary to create an observation and interference program with this children, as well as orientation and assistance of the family so that it is possible to contribute to the global development of lead-intoxicated children.